Comparative effectiveness of combined favipiravir and oseltamivir therapy versus oseltamivir monotherapy in critically ill patients with influenza virus infection - Wang, Y; Fan, G; Salam, A; Horby, P; Hayden, F; Chen, C; Pan, J; Zheng, J; Lu, B; Guo, L; Wang, C; Cao, B; et al. (Oxford University Press, 2019)
Background A synergistic effect of combination therapy with favipiravir and oseltamivir has been reported in preclinical models of influenza. However, no data are available on the clinical effectiveness of combination therapy in severe influenza.